The effect of flue-curing and redrying on the diversity of fungal communities in tobacco leaves - Yue Yang; Gaowei Pan; Jianhua Guo; Chenlin Miao; Qiang Xu; Yifan Zhang; Mengmeng Yang; Chaoqun Xue; Liwei Hu; Zongyu Hu (BMC Microbiology)
Abstract Flue-curing and redrying are important processing stages before tobacco fermentation, closely linked to microbial actions that influence the fermentation process. It is necessary to investigate the effects of flue-curing and redrying on diversity and succession of tobacco fungal communities. It was shown that a total of 9 phyla, 33 classes, 94 orders, 266 families, 646 genera, and 6,396 amplicon sequence variants (ASVs) were identified in the fungi communities of 36 samples from different processing stages (before flue-curing, after flue-curing, before redrying and after redrying) based on high-throughput sequencing technology. Dominant genera shared by tobacco leaves at different stages were Alternaria and Sampaiozyma. About 80% of fungi in stored tobacco leaves after redrying originated from fresh tobacco leaves before flue-curing, while the rest were primarily enriched in the post-harvest processing environment. After flue-curing, major molds like Aspergillus and Penicillium were notably enriched. The distribution of fungal communities suggested that the flue-curing and redrying had a significant impact on fungal composition. Functional annotation of fungal communities at the guild level exhibited differences during processing stages. Main fungal functional groups were identified. In summary, our study elucidated dynamic changes in the composition of fungal communities and highlighted key stages in mold enrichment during tobacco leaf processing, laying groundwork for mildew prevention and control during tobacco leaf fermentation.